2015
DOI: 10.1098/rsos.140426
|View full text |Cite
|
Sign up to set email alerts
|

Rapid nectar-meal effects on a predator's capacity to kill mosquitoes

Abstract: Using Evarcha culicivora, an East African jumping spider (Salticidae), we investigate how nectar meals function in concert with predation specifically at the juvenile stage between emerging from the egg sac and the first encounter with prey. Using plants and using artificial nectar consisting of sugar alone or sugar plus amino acids, we show that the plant species (Lantana camara, Ricinus communis, Parthenium hysterophorus), the particular sugars in the artificial nectar (sucrose, fructose, glucose, maltose), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 69 publications
(76 reference statements)
0
6
0
Order By: Relevance
“…culicivora in the period between emerging from the egg sac and the first encounter with prey was later confirmed by Carvell et al . (). Additional studies are necessary to determine the significance of nectar feeding for spiders along their development.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…culicivora in the period between emerging from the egg sac and the first encounter with prey was later confirmed by Carvell et al . (). Additional studies are necessary to determine the significance of nectar feeding for spiders along their development.…”
Section: Discussionmentioning
confidence: 97%
“…They concluded by means of choice tests done with spiders that sugar, and not just water, is relevant to salticids because these spiders spent more time drinking from a simulated nectar source (30% sucrose solution) than from distilled water during the experiment. In addition, Carvell, Kuja & Jackson () showed that consumption of sugar (sucrose, fructose, glucose and maltose) by Evarcha culicivora (Salticidae) juveniles in artificial diets influence positively spider's prey‐capture proficiency on the next day after the nectar meal. However, probably water is also important in Cerrado, since it is a relatively hot and dry environment, and spiders are sensible to desiccation (Pulz, ).…”
Section: Discussionmentioning
confidence: 99%
“…In laboratory olfactometer experiments (Cross and Jackson, 2009b), adult females, adult males and juveniles from all size classes were attracted to the odour of two plant species, L. camara and R. communis . The juveniles of E. culicivora are especially inclined to feed on nectar when they visit plants (Kuja et al, 2012) and there is a specialized relationship between nectar meals and predation on mosquitoes: after nectar meals, the juveniles of E. culicivora become more effective at subduing the mosquitoes they attack (Carvell and Jackson, 2015). However, we propose that mating instead of feeding is the context in which E. culicivora adults make specialized use of plants.…”
Section: Discussionmentioning
confidence: 99%
“…‘Plant specialist’ is another convenient expression when discussing E. culicivora but progress at understanding what plants, especially L. camara and R. communis , mean to this spider has been slow in comparison to advances in our understanding of specialization on mosquitoes. Earlier research suggests that visiting plants has different functions depending on whether the spider is an adult or a juvenile, with juveniles using plants primarily as food sources (Kuja et al, 2011; Carvell et al, 2015) and adults using plants as mating sites (Cross et al, 2008). However, our experiments here were designed to examine what plants mean to E. culicivora from a different perspective.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation